2020
DOI: 10.3390/fluids5030132
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Fountain Formation due to Normal and Inclined Twin-Jet Impingement on Ground

Abstract: The goal of this paper is to study numerically the flow physics of a fountain formed by twin-jet impingement on ground. The incompressible Reynolds-Averaged Navier-Stokes (RANS) equations with realizable k-ε and WA (Wray-Agarwal) turbulence model are employed in the numerical simulations with ANSYS Fluent. A series of numerical simulations for straight and inclined fountain formations are conducted by changing the geometric and flow parameters of twin jets and distance between them. The changes in parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Through CFD technology, scholars can also carry out research on the unsteady flow process of water jets. Based on the incompressible Reynolds-averaged Navier-Stokes (RANS) equations with the W-A turbulence model, Zhang et al [21] carried out numerical simulation of single-jet impingement. The results showed that the W-A model has good applicability in numerical simulation of single-jet impingement.…”
Section: Introductionmentioning
confidence: 99%
“…Through CFD technology, scholars can also carry out research on the unsteady flow process of water jets. Based on the incompressible Reynolds-averaged Navier-Stokes (RANS) equations with the W-A turbulence model, Zhang et al [21] carried out numerical simulation of single-jet impingement. The results showed that the W-A model has good applicability in numerical simulation of single-jet impingement.…”
Section: Introductionmentioning
confidence: 99%